Pengaruh Pencampuran Eco Racing Dengan Bahan Bakar Pertalite dan Pertamax Pada Performa Sepeda Motor 125 CC - Iqumuddin, Moch; Bahri, Mokh Hairul; Nusantara, Ardhi Fathoni Syam Putra (Journal of Engineering Science and Technology, 2023)
Fuel is one of the main needs of motorized vehicles. Most motorbike riders want the fuel they use to produce greater torque and power than standard specifications with lower exhaust emissions but save fuel. For this reason, several alternative solutions are needed to overcome this problem, including the use of additives, one of which is eco racing. The aim of this research is to determine the effect of adding eco racing to fuel variations on torque, power and exhaust emissions of 125 CC motorbikes. The research approach was carried out quantitatively by conducting descriptive analytical experiments. Data collection was carried out with various fuel variations at several engine rotation speeds. The research results showed that the mixture of Pertalite with 1 Eco Racing tablet and Pertalite with 2 Eco Racing tablets did not have much effect on power and torque, but increased exhaust emissions. Then, a mixture of Pertamax with 1 Eco Racing tablet and 2 Eco Racing tablets also does not really increase power and torque, but does increase exhaust emissions. The expected result of this research is to determine the effect of adding eco racing on engine performance. From the test results it was found that the addition of eco racing did not increase power and torque, but instead increased exhaust emissions.